A Survey of Insect Pests Attacking Quinoa (Chenopodium quinoa) and Their Natural Enemies in Zimbabwe - Dube, Onias; Mudada, Nhamo; Gama, Tsvakai; Muziri, Tavagwisa (Science Publishing Group, 2022)
Quinoa (Chenopodium quinoa Wild.) was first introduced in Zimbabwe in 2017. As a new crop introduction, studies to understand the agronomic and biotic factors affecting quinoa cultivation are needed. A study to identify pests associated with quinoa production was therefore carried out at Midlands State University farm in Zimbabwe. A survey was conducted to determine the presence and populations of insect pests attacking quinoa crop during production. Field scouting of five (5) tagged plants per plot was done using canopy observation, buttressed with sticky and pitfall traps. Sampling was done when 50% of the crop had reached key physiological stages i.e early vegetative stage, vegetative stage, flowering, milk dough stage, dough stage, physiological maturity and at harvest. The most abundant pests observed were aphids, brown stink bugs, grasshoppers, and lepidopteron bollworms. Natural enemies observed were black ants, brown ants and ladybird beetles. Signs of insect damage observed include weakening of panicles, chlorosis of leaves, leaf eating and sooty mould development on the panicles. Findings of the study showed that quinoa attracts a diversity of leaf eating and sap sucking insects. This is the first study of insect pests associated with quinoa in Zimbabwe, and the results of the study indicate the need to develop insect pest management strategies for quinoa production in the country